EXPLORING THE NOTARY LIABILITY IN TORTS (An Exclusive Interview with the Chairman of the Indonesian Notary Association of Batam City) - Triana Dewi Seroja; Nurlaily Nurlaily; Rina Shahriyani Shahrullah; Nur Hadiyati; Kwariyon Altison (Universitas Slamet Riyadi, 2021)
In practice, it often occurs that a notary is summoned to the court on the ground that he/she provides information on the deeds or documents containing torts (an act against the law). This study questions whether a notary is liablewhen the torts occur. This study utilizes a socio-legal research method by adopting qualitative juridical data analysis. It found thattorts may occur due to 2 (two) factors, namely (1) lack of precaution when drafting the deeds, and (2) deliberatelymaking the deeds which do not meet the specified conditions. As the results, the notary is liable to bear all losses arising from the issuing of the deed, including a liability due to a criminal lawsuit. In order to prevent torts, a notary mustdisclose all relevant information, clarify documents, and have more legal awareness.